Analisis Pengaruh Infrastruktur Jalan, Listrik Dan Air Terhadap Produk Domestik Regional Bruto (PDRB) Kota Bandar Lampung Di Tinjau Dari Perspektif Ekonomi Islam Tahun 2011-2024 - Salsabila, Afifah Dhafa; Putri, Rosydalina; Ermawati, Liya (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
Infrastructure is a fundamental facility that plays a vital role in supporting the social and economic activities of society. Infrastructure such as roads, electricity, and clean water serves as the main foundation for production, distribution, and consumption activities within a region. The availability of adequate infrastructure is a key factor in enhancing economic efficiency, expanding access to public services, and strengthening regional competitiveness. This study aims to analyze the influence of road, electricity, and water infrastructure on the Gross Regional Domestic Product (GRDP) of Bandar Lampung City for the period 2011–2024 from an Islamic economic perspective. The research employs a quantitative descriptive approach using multiple linear regression analysis (time series), with secondary data obtained from the Central Bureau of Statistics (BPS), PLN, PDAM, and the Public Works Department of Bandar Lampung City. The population in this study consists of road, electricity, and water infrastructure as well as the GRDP of Bandar Lampung City. Thus, the sample analyzed comprises 14 observations from 2011 to 2024. The data were processed and analyzed using EViews 12 software, which includes classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) and hypothesis testing (t-test, F-test, and coefficient of determination). The results indicate that simultaneously, the three infrastructure variables have a significant effect on GRDP with an Adjusted R-squared value of 0.807 or 80.7%, meaning that 80.7% of GRDP variation can be explained by road, electricity, and water infrastructure variables, while the remaining 19.3% is influenced by other variables outside the study. Partially, road and electricity infrastructure significantly affect GRDP, while water infrastructure has a positive but insignificant effect. The classical assumption tests show that the data meet the criteria for a good regression model, as all tests indicate normality and the absence of multicollinearity, heteroscedasticity, and autocorrelation. From an Islamic economic perspective, infrastructure development is a mandate of the khalifah (leader) to prosper the earth in accordance with the principles of maslahah (public benefit), justice, and social responsibility. Therefore, equitable and sustainable infrastructure development can promote economic growth and community welfare